Orthopedic Frailty Score and adverse outcomes in patients with surgically managed isolated traumatic spinal injury - Yang Cao; Shahin Mohseni; Babak Sarani; Frank Hildebrand; Ahmad Mohammad Ismail; Maximilian Peter Forssten; Parker Chang; Marcelo A F Ribeiro (Trauma Surgery & Acute Care Open)
Background With an aging global population, the prevalence of frailty in patients with traumatic spinal injury (TSI) is steadily increasing. The aim of the current study is to evaluate the utility of the Orthopedic Frailty Score (OFS) in assessing the risk of adverse outcomes in patients with isolated TSI requiring surgery, with the hypothesis that frailer patients suffer from a disproportionately increased risk of these outcomes.Methods The Trauma Quality Improvement Program database was queried for all adult patients (18 years or older) who suffered an isolated TSI due to blunt force trauma, between 2013 and 2019, and underwent spine surgery. Patients were categorized as non-frail (OFS 0), pre-frail (OFS 1), or frail (OFS ≥2). The association between the OFS and in-hospital mortality, complications, and failure to rescue (FTR) was determined using Poisson regression models, adjusted for potential confounding.Results A total of 43 768 patients were included in the current investigation. After adjusting for confounding, frailty was associated with a more than doubling in the risk of in-hospital mortality (adjusted incidence rate ratio (IRR) (95% CI): 2.53 (2.04 to 3.12), p<0.001), a 25% higher overall risk of complications (adjusted IRR (95% CI): 1.25 (1.02 to 1.54), p=0.032), a doubling in the risk of FTR (adjusted IRR (95% CI): 2.00 (1.39 to 2.90), p<0.001), and a 10% increase in the risk of intensive care unit admission (adjusted IRR (95% CI): 1.10 (1.04 to 1.15), p=0.004), compared with non-frail patients.Conclusion The findings indicate that the OFS could be an effective method for identifying frail patients with TSIs who are at a disproportionate risk of adverse events.Level of evidence Level III.